Evaluation of in vitro storage characteristics of cold stored platelet concentrates with N acetylcysteine (NAC). Issue 1 (February 2016) - Handigund, Mallikarjun; Bae, Tae Won; Lee, Jaehyeon; Cho, Yong Gon
Abstract: Platelets play a vital role in hemostasis and thrombosis, and their demand and usage has multiplied many folds over the years. However, due to the short life span and storage constraints on platelets, it is allowed to store them for up to 7 days at room temperature (RT); thus, there is a need for an alternative storage strategy for extension of shelf life. Current investigation involves the addition of 50 mM N acetylcysteine (NAC) in refrigerated concentrates. Investigation results revealed that addition of NAC to refrigerated concentrates prevented platelet activation and reduced the sialidase activity upon rewarming as well as on prolonged storage. Refrigerated concentrates with 50 mM NAC expressed a 23.91 ± 6.23% of CD62P (P-Selectin) and 22.33 ± 3.42% of phosphotidylserine (PS), whereas RT-stored platelets showed a 46.87 ± 5.23% of CD62P and 25.9 ± 6.48% of phosphotidylserine (PS) after 5 days of storage. Further, key metabolic parameters such as glucose and lactate accumulation indicated reduced metabolic activity. Taken together, investigation and observations indicate that addition of NAC potentially protects refrigerated concentrates by preventing platelet activation, stabilizing sialidase activity, and further reducing the metabolic activity. Hence, we believe that NAC can be a good candidate for an additive solution to retain platelet characteristics during cold storage and may pave the way for extension of storage shelf life.